2007
DOI: 10.1134/s0006297907020010
|View full text |Cite
|
Sign up to set email alerts
|

Lysophospholipid receptors in cell signaling

Abstract: There is increasing evidence that different phospholipids are involved in regulation of various cell processes and cell-cell interactions. Lysophospholipids (lysophosphatidic acid, lysophosphatidylcholine) and a number of lysosphingolipids play particular roles in these regulations. Their effects are mediated by specific G-protein-coupled receptors. G-Protein coupled signal transduction to the cell nucleus involving a chain of intracellular protein kinases induces the main effects in cells--growth, proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…An alternative mechanism through which exogenous PA activates ERK and mTORC1 is through its hydrolysis to LPA by phospholipases (i.e., phospholipase A) present in the culture medium, followed by subsequent binding of LPA to endothelial differentiation gene (EDG) receptors. Activation of EDG receptors would then lead to increased signaling through the MEK-ERK pathway (52). Phospholipase A is present in serum (35) and is also secreted by cells in culture (27,39).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative mechanism through which exogenous PA activates ERK and mTORC1 is through its hydrolysis to LPA by phospholipases (i.e., phospholipase A) present in the culture medium, followed by subsequent binding of LPA to endothelial differentiation gene (EDG) receptors. Activation of EDG receptors would then lead to increased signaling through the MEK-ERK pathway (52). Phospholipase A is present in serum (35) and is also secreted by cells in culture (27,39).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that some LPLs act in a wide range of animal cells as growth factors with hormone-like biological activities. They initiate and regulate cell proliferation including mitosis, cell differentiation and migration, and affect cell viability through anti-apoptosis properties (Birgbauer and Chun, 2006;Torkhovskaya et al, 2007). Considering their role among metazoans, one hypothesis is that they act as signaling molecules or metabolic intermediates during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, lysophospholipids (LPLs) represent only 0.5 to 6% of the whole PL content of cell membranes (Birgbauer and Chun, 2006;Torkhovskaya et al, 2007), their structural role being considered minor. However, they are recognized as second messenger molecules in cellular signal transduction processes (Torkhovskaya et al, 2007;D'Arrigo and Servi, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that lyso-PC bind and activate G protein-coupled receptor (GPCR) [30]. To test the involvement of GPCR on lyso-PC signaling, peritoneal macrophages from both wild-type and TLR2 Ϫ/Ϫ mice were treated with the Gai inhibitor, pertussis toxin (100 ng/mL), for 30 min before treatment with lyso-PC.…”
Section: S Mansoni-induced Eosinophil Recruitment and Activation Occmentioning
confidence: 99%